Peningkatan Kemampuan Berwirausaha melalui Program PPK Ormawa: Implementasi Diversifikasi Produk Pisang di Desa Punggur Besar - Gunawan, Syahrul; Taufik, Muhammad Iman; Cahyo, Gusti Septian Dwi; Febriyanti, Hana; Syahlidi, Goku; Hani, Siti Nurhafizah; Yanti, Feby Dwi; Romadhon, Mohamad Rafli (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The implementation of community service in Punggur Besar village focuses on diversifying processed banana fruit as a village potential, through mentoring and empowerment activities for Punggur Besar villagers. This activity aims to improve knowledge and skills as well as increase the income of the Punggur Besar Village PKK women's group through diversification of banana fruit products. The method of implementing this activity was carried out by providing socialization, training and assistance in diversifying processed banana fruit products from the production process to marketing. The results of the activity showed an increase in the productivity of Punggur Besar villagers in making processed banana fruit, having skills in entrepreneurship independently and being able to increase the growth of village MSMEs.